alcru
alcru
04-04-2016
Mathematics
contestada
what is y = (x-6)^2 - 2 in y = ax^2+bx+c form
Respuesta :
Panoyin
Panoyin
04-04-2016
y = (x - 6)² - 2
y = (x - 6)(x - 6) - 2
y = (x(x - 6) - 6(x - 6)) - 2
y = (x(x) - x(6) - 6(x) + 6(6)) - 2
y = (x² - 6x - 6x + 36) - 2
y = (x² - 12x + 36) - 2
y = x² - 12x + 36 - 2
y = x² - 12x + 34
Answer Link
apologiabiology
apologiabiology
04-04-2016
easy, just expand
y=(x-6)^2-2
y=(x-6)(x-6)-2
y=x^2-6x-6x+36-2
y=x^2-12x+34
y=ax^2+bx+c
a=1
b=-12
c=34
Answer Link
VER TODAS LAS RESPUESTAS ( 19+ )
Otras preguntas
Write a proportion for each of the following equations and perform all changes: 2·9=3·6 I don't need a straight-up answer, I need an explanation of how to do th
PLZZZ HELP ME WHAT DOES x=?????? WHOEVER ANSWERS FORST GETS BRAINLIEST THANKYOUUU
themes of expressionism
By this time next year, I ----- all my exams.
Puede alguien ayudarme a entender con el paso a paso cómo resolver estos ejercicios de derivadas (estadísticas), gracias.
8:3 and 5:2 equivalent
Which of the following is an example of an unhealthy online behavior? A. Posting photos of yourself drinking alcohol B. Posting your reviews of movies you've se
I need help with this
How many congrees members
which of the following is a leg exercise? A. lunges B. lap pull-downs C. upright rows D. dips